KUALITAS PELAYANAN PERPUSTAKAAN BERBASIS INKLUSI SOSIAL - Saban, Ade Muhammad; Sudarsa, Agus Suarman; Subagdja, Oetje (Universitas Djuanda, 2022)
Libraries with the concept of social inclusion, apart from being a place for reading, can also channel ideas through activities, training, and coaching. This research aims to determine the quality of library services with the concept of social inclusion in the city of Sukabumi. The use of theory in this study is based on service quality. The method used is qualitative with a unit of analysis descriptive approach. This research has results that show a quality of service with the concept of social inclusion in Sukabumi City, which is said to be good; this is indicated by the accreditation status, which achieves an A value. It can be indicated by the dimensions of service quality, including tangible, which is characterized by a strategic library location and the availability of facilities and infrastructure adequate; reliability is characterized by the existence of a service flow that is not convoluted and is supported by service officers who always serve on time, Responsiveness is characterized by the presence of speed of officers in responding to various needs or complaints from the community, characterized by the presence of service officers who are always ready standby is in every room and assurance can be described by having extensive knowledge of officers, officers having outstanding ethics and being honest in providing services.